NPM1 ablation induces HSC aging and inflammation to develop myelodysplastic syndrome exacerbated by p53 loss. (1st March 2022) - Morganti, Claudia; Ito, Kyoko; Yanase, Chie; Verma, Amit; Teruya‐Feldstein, Julie; Ito, Keisuke
Abstract: Myelodysplastic syndrome (MDS) is characterized by ineffective hematopoiesis with morphologic dysplasia and a propensity to transform into overt acute myeloid leukemia (AML). Our analysis of two cohorts of 20 MDS and 49 AML with multi‐lineage dysplasia patients shows a reduction in Nucleophosmin 1 ( NPM1 ) expression in 70% and 90% of cases, respectively. A mouse model of Npm1 conditional knockout (cKO) in hematopoietic cells reveals that Npm1 loss causes premature aging of hematopoietic stem cells (HSCs). Mitochondrial activation in Npm1 ‐deficient HSCs leads to aberrant activation of the NLRP3 inflammasome, which correlates with a developing MDS‐like phenotype. Npm1 cKO mice exhibit shortened survival times, and expansion of both the intra‐ and extra‐medullary myeloid populations, while evoking a p53‐dependent response. After transfer into a p53 mutant background, the resulting Npm1 / p53 double KO mice develop fatal leukemia within 6 months. Our findings identify NPM1 as a regulator of HSC aging and inflammation and highlight the role of p53 in MDS progression to leukemia. SYNOPSIS: Mitochondrial alterations and increased inflammation in Npm1 cKO mice result in HSC aging and MDS‐like phenotypes. p53 dependent responses in Npm1 cKO mice lead to bone marrow failure, while Npm1/p53 double KO mice develop leukemia. MDS and MLD in AML patients show reduced levels of NPM1. Npm1 loss causes mitochondrial activation, triggering the NLRP3 inflammasome and premature aging of HSCs. The p53‐dependent response induced by Npm1 loss results in bone marrow failure. Npm1/p53 double KO mice develop fatal leukemia within 6 months. Abstract : Mitochondrial alterations and increased inflammation in Npm1 cKO mice result in HSC aging and MDS‐like phenotypes. p53 dependent responses in Npm1 cKO mice lead to bone marrow failure, while Npm1/p53 double KO mice develop leukemia.